The influence of contextual approach to students’ problem solving ability of Class IX of SMP Negeri 1 Bayang - Yerizon, Yerizon; Ahda, Yuni; Amsari, Dina (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
The purpose of this study was to investigate the effect of student’s problem solving abilities with contextual approaches. Student’sproblem solving ability is still low because the teacher does not associate mathematics material with student's real world situations. In addition, students are also less active especially to find mathematical concepts. To overcome this problem, a Contextual Approach was applied in mathematics learning. This research is a quasi-experimental research using a quantitative approach. The research population was students of grade IX students at SMPN 1 Bayang. The used technique for sampling is random sampling. The research sample was of class IX.2 as an experimental class and class IX.3 as a control class. The used instrument was a problem solving ability test and questionnaire. Data obtained through tests were analyzed using two-way variance analysis. The results showed that the average test scores of student’s problem solving ability in experimental class was higher than the control class for high and low initial abilities. It can be concluded that problem solving abilities can be improved by using contextual learning.